Sodium-ion-conductive glass ceramic

The sodium ion conductive glass ceramic, with its optimized composition and monoclinic crystalline phase, addresses the challenge of hydrogen gas generation in aqueous sodium ion secondary batteries by providing a dense structure, high water shielding, and enhanced sodium ion conductivity.

JP2025069819APending Publication Date: 2025-05-01OHARA INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023179785
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

Aqueous sodium ion secondary batteries face challenges in suppressing hydrogen gas generation during charging, which leads to polarization and difficulties in current flow due to the lack of effective sodium ion conductive materials with high water shielding properties.

Method used

Development of a sodium ion conductive glass ceramic with a dense structure, high water shielding properties, and high sodium ion conductivity, achieved by optimizing the composition ratio of Na, Zr, P, and Si, and incorporating a monoclinic crystalline phase with a crystalline phase ratio of less than 10% by mass.

Benefits of technology

The sodium ion conductive glass ceramic effectively suppresses hydrogen gas generation, enhances water shielding, and improves sodium ion conductivity, making it suitable for use in electrolyte diaphragms for aqueous sodium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069819000007
    Figure 2025069819000007
  • Figure 2025069819000008
    Figure 2025069819000008
  • Figure 2025069819000009
    Figure 2025069819000009
Patent Text Reader

Abstract

To provide a sodium-ion-conductive glass ceramic which has a dense structure, high water shielding properties, and high sodium ion conductivity and can be used in an electrolyte diaphragm for an aqueous sodium-ion secondary battery.SOLUTION: The problem is solved by a sodium-ion-conductive glass ceramic containing, in mol% in terms of oxide, 20.0-27.0% of a Na2O component, 30.0-40.0% of a ZrO2 component, 3.0-20.0% of a P2O5 component, and 20.0-40.0% of a SiO2 component, and including a monoclinic crystal phase represented by Na1+xZr2SixP3-xO12 (0<X<3), wherein the proportion of a ZrO2 crystal phase in all crystal phases included is at most 10 mass%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sodium ion conductive glass-ceramic, an electrolyte membrane for an aqueous sodium ion secondary battery containing the same, and a glass material used in the synthesis of the sodium ion conductive glass-ceramic. [Background technology]

[0002] Currently, lithium-ion secondary batteries are widely used as power sources for electric vehicles, mobile phone terminals, etc. Furthermore, mainly from the perspective of improving safety, development is also underway for all-solid-state secondary batteries, in which the electrode layers and electrolyte layers are all made of inorganic solids, as lithium-ion secondary batteries that do not use liquid electrolytes (electrolytic solutions).

[0003] However, lithium, an essential component of lithium-ion secondary batteries, is not an abundant resource, and therefore poses problems in terms of cost, supply, etc. Therefore, sodium, which is an abundant and inexpensive resource, has attracted attention, and sodium-ion secondary batteries containing aqueous electrolytes (aqueous sodium-ion secondary batteries) have been developed (e.g., Patent Documents 1 to 4).

[0004] Water-based sodium-ion secondary batteries have an advantage in terms of cost because they can use sodium, which is abundant in seawater, as a raw material, and are also considered promising from the perspective of ease of securing resources.In addition, regarding safety, which becomes an issue when the battery is made larger, aqueous electrolytes are extremely difficult to ignite, while the organic solvent electrolytes commonly used in lithium-ion secondary batteries have a flash point of about 140°C, so it is expected that safety can be improved. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2011-086402 A [Patent Document 2] JP 2012-003928 A [Patent Document 3] JP 2012-054208 A [Patent Document 4] JP 2017-124951 A Summary of the Invention [Problem to be solved by the invention]

[0006] Here, in the case of aqueous alkali metal ion secondary batteries containing an aqueous electrolyte, there is a problem that hydrogen gas is generated by electrolysis of water during charging. In particular, although aqueous sodium ion secondary batteries are advantageous in terms of cost as described above, it is said that it is difficult to suppress the generation of hydrogen gas during charging no matter what negative electrode active material is used, and if this generated hydrogen gas remains on the negative electrode, it becomes difficult for a current to flow due to polarization.

[0007] In order to solve this problem, that is, to obtain an aqueous alkali metal ion secondary battery having a high electromotive force while suppressing the generation of hydrogen gas, etc., for example, an aqueous lithium ion secondary battery has been devised in which a lithium ion solid electrolyte that has high water impermeability, lithium ion conductivity, and water resistance is disposed between the positive electrode and the negative electrode as an electrolyte separator. However, for sodium ion conducting materials, Na3Zr2Si2PO 12 However, it is known that this has poor sintering properties and cannot provide a dense electrolyte membrane with high water impermeability. 12 A method has been disclosed in which the voids in a molded body (connected body) are impregnated with a molten hydrocarbon compound (resin), and the surface is finally subjected to plasma treatment to obtain a highly water-impermeable sodium ion conductive material that exhibits sodium ion conductivity. This method is based on the concept of filling the voids with a hydrocarbon compound, Na3Zr2Si2PO 12 Therefore, the sodium ion conductivity is not high, and since it contains a hydrocarbon compound with low durability, the sodium ion conductivity is high. 12There is an extremely high possibility that long-term water barrier properties cannot be obtained at the joint surface with others, etc.

[0008] Therefore, an object of the present invention is to provide sodium ion conductive glass ceramics that can be used for an electrolyte separator for an aqueous sodium ion secondary battery, which has a dense structure, high water barrier properties, and high sodium ion conductivity.

Means for Solving the Problems

[0009] In order to solve the above problems, the present inventors have intensively studied, and in terms of mol% in terms of oxides, the Na2O component is 20.0 to 27.0%, the ZrO2 component is 30.0 to 40.0%, the P2O5 component is 3.0 to 20.0%, and the SiO2 component is 20.0 to 40.0%. It contains Na 1+x Zr2Si x P 3-x O 12 By using sodium ion conductive glass ceramics containing a monoclinic crystal phase represented by (0 < X < 3) and having a proportion of ZrO2 crystal phase of 10% by mass or less among all the contained crystal phases, it has a dense structure, high water barrier properties, and high sodium ion conductivity, and has been found to be suitably used for an electrolyte separator for an aqueous sodium ion secondary battery, thus completing the present invention.

[0010] That is, the present invention is as follows <1> to <9>. <1> In terms of mol% in terms of oxides, the Na2O component is 20.0 to 27.0%, the ZrO2 component is 30.0 to 40.0%, the P2O5 component is 3.0 to 20.0%, and the SiO2 component is 20.0 to 40.0%. It contains Na 1+x Zr2Si x P 3-x O 12 Sodium ion conductive glass ceramics containing a monoclinic crystal phase represented by (0 < X < 3) and having a proportion of ZrO2 crystal phase of 10% by mass or less among all the contained crystal phases. <2> In the sodium ion conductive glass ceramics, the composition ratio of Na, Zr, P, and Si is Na 1+x Zr2Si x P3-x O 12 The sodium ion conductive glass ceramics according to <1>, which satisfy the composition ratio represented by (0 < X < 3). <3> When the sodium ion conductive glass ceramics are used as a sheet-like or plate-like substrate, the leakage rate per unit area and per 1 mm thickness of the substrate is 10.0 μL / h or less, or the current amount when electrolysis of water caused by the water leaked per unit area and per 1 mm thickness of the substrate per hour occurs is 15 μA or less per unit area and per 1 mm thickness of the substrate. The sodium ion conductive glass ceramics according to <1> or <2>. <4> The sodium ion conductivity at 25 °C is 6.0×10 -4 S / cm or more. The sodium ion conductive glass ceramics according to any one of <1> to <3>. <5> A glass material powder having a sodium ion conductivity at 25 °C of 1.0×10 -6 S / cm or less, and a crystalline material powder containing a ZrO2 component having a sodium ion conductivity at 25 °C of less than 1.0×10 -8 S / cm. The sodium ion conductive glass ceramics according to any one of <1> to <4>, which are obtained by mixing and sintering these. <6> Among all the crystal phases contained, the proportion of the monoclinic crystal phase represented by the formula (0 < X < 3) is 70% by mass or more. The sodium ion conductive glass ceramics according to any one of <1> to <5>. 1+x Na x Zr2Si 3-x P 12 O <7> The proportion of the amorphous phase is 10% by mass or more. The sodium ion conductive glass ceramics according to any one of <1> to <6>. <8> An electrolyte separator for an aqueous sodium ion secondary battery, which contains the sodium ion conductive glass ceramics according to any one of <1> to <7>. In mol% in terms of oxide, it contains 30.0 to 40.0% of Na2O component, 0 to 5.0% of ZrO2 component, 5.0 to 35.0% of P2O5 component, and 30.0 to 60.0% of SiO2 component, and the composition ratio of Na, P, and Si satisfies the composition ratio excluding Zr among the composition ratios represented by Na 1+x Zr2Si x P 3-x O 12 A glass material for synthesizing sodium ion conductive glass ceramics that satisfies the composition ratio excluding Zr among the composition ratios represented by (0 < X < 3).

Advantages of the Invention

[0011] According to the present invention, it is possible to provide sodium ion conductive glass ceramics having a dense structure, high water barrier property, and high sodium ion conductivity. And, by using this sodium ion conductive glass ceramics, it is possible to provide an excellent electrolyte diaphragm for aqueous sodium ion secondary batteries.

Brief Description of the Drawings

[0012] [Figure 1] It is a schematic diagram of an apparatus (pellet leak checker using water column pressure) for measuring the water barrier property used in the examples. [Diagram 2] It is a graph showing the water barrier property measurement results of Comparative Example 2 and Example 3. [Diagram 3] It is a graph showing the powder X-ray diffraction measurement results of the sintered body pellet of Example 3. [Figure 4] It is a secondary electron image of the fracture surface of the sintered body pellet of Comparative Example 1 (photograph for substitute of drawing). [Diagram 5] It is an enlarged view of the secondary electron image of FIG. 4 (photograph for substitute of drawing). [Figure 6] It is a secondary electron image of the fracture surface of the sintered body pellet of Comparative Example 2 (photograph for substitute of drawing). [Figure 7] It is an enlarged view of the secondary electron image of FIG. 6 (photograph for substitute of drawing). [Figure 8] It is a secondary electron image of the fracture surface of the sintered body pellet of Example 3 (photograph for substitute of drawing). [Figure 9]It is an enlarged view of the secondary electron image of FIG. 8 (photograph substituting for drawing). [Figure 10] It is a backscattered electron image of the fracture surface in the sheet-like sintered body of Example 5 (photograph substituting for drawing). [Figure 11] It is a backscattered electron image of the fracture surface in the sheet-like sintered body of Comparative Example 3 (photograph substituting for drawing).

Mode for Carrying Out the Invention

[0013] The present invention will be described. The present invention contains, in terms of mol% in terms of oxide, 20.0 to 27.0% of Na2O component, 30.0 to 40.0% of ZrO2 component, 3.0 to 20.0% of P2O5 component, and 20.0 to 40.0% of SiO2 component, and Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) contains a monoclinic crystal phase represented by, and among all the crystal phases contained, the proportion of the ZrO2 crystal phase is 10% by mass or less, and is a sodium ion conductive glass ceramic, and is also an electrolyte diaphragm for an aqueous sodium ion secondary battery containing the same. In the following, these may also be referred to as "the sodium ion conductive glass ceramic of the present invention" and "the electrolyte diaphragm for an aqueous sodium ion secondary battery of the present invention". Further, the present invention contains, in terms of mol% in terms of oxide, 30.0 to 40.0% of Na2O component, 0 to 5.0% of ZrO2 component, 5.0 to 35.0% of P2O5 component, and 30.0 to 60.0% of SiO2 component, and the composition ratio of Na, P, and Si satisfies the composition ratio excluding Zr among the composition ratios represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3), and also includes a glass material for synthesizing a sodium ion conductive glass ceramic. In the following, this may also be referred to as "the glass material for synthesizing a sodium ion conductive glass ceramic of the present invention".

[0014] In addition, unless otherwise specified, the content of the components contained in the sodium ion-conductive glass ceramics of the present invention and the glass material for synthesizing the sodium ion-conductive glass ceramics of the present invention is expressed in mol% in terms of oxide (hereinafter, unless otherwise specified, simply referred to as mol% also means mol% in terms of oxide). The content expressed in this "mol% in terms of oxide" means that when it is assumed that oxides, double salts, metal fluorides, etc. used as raw materials for the sodium ion-conductive glass ceramics of the present invention and the glass material for synthesizing the sodium ion-conductive glass ceramics of the present invention are all decomposed into oxides during melting, with the total number of moles of the generated oxides being 100 mol%, the content of the oxides of each component contained in the sodium ion-conductive glass ceramics of the present invention or the glass material for synthesizing the sodium ion-conductive glass ceramics of the present invention is described.

[0015] <Constituent Components and Composition of Sodium Ion-Conductive Glass Ceramics> First, the components and composition constituting the sodium ion-conductive glass ceramics of the present invention will be described in detail.

[0016] The Na2O component is an essential component necessary to impart sodium ion conductivity to the sodium ion-conductive glass ceramics of the present invention. That is, Na that greatly contributes to sodium ion conductivity 1+x Zr2Si x P 3-x O 12 It can also be said to be an essential component that forms a monoclinic crystal phase represented by (0 < X < 3). Therefore, the content of the Na2O component has a lower limit of 20.0 mol%, preferably 21.0 mol%, more preferably 22.0 mol%, still more preferably 22.5 mol%, and still more preferably 23.0 mol%. On the other hand, Na 1+x Zr2Si x P 3-x O 12 Since it becomes easier to form a monoclinic crystal phase represented by (0 < X < 3), etc., the content of the Na2O component has an upper limit of 27 mol%, preferably 26.0 mol%, and more preferably 25.0 mol%.

[0017] The P2O5 component is an essential component necessary for the sodium ion conductive glass ceramics of the present invention to contain a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) and to have excellent sodium ion conductivity. Therefore, the content of the P2O5 component is 3.0 mol%, preferably 5.0 mol%, more preferably 8.0 mol% as the lower limit. Also, Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is likely to form a monoclinic crystal phase, etc., so the content of the P2O5 component is 20.0 mol%, preferably 18.0 mol%, more preferably 16.0 mol%, even more preferably 14.0 mol%, even more preferably 12.0 mol%, even more preferably 10.0 mol% as the upper limit.

[0018] The ZrO2 component is an essential component necessary for the sodium ion conductive glass ceramics of the present invention to contain a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) and to have excellent sodium ion conductivity. Also, it contributes to improving the water resistance of the sodium ion conductive glass ceramics of the present invention. Therefore, the content of the ZrO2 component is 30.0 mol%, preferably 31.0 mol%, more preferably 33.0 mol% as the lower limit. Also, Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is likely to form a monoclinic crystal phase and is likely to reduce the proportion of the ZrO2 crystal phase, etc., so the content of the ZrO2 component is 40.0 mol%, preferably 39.0 mol%, more preferably 37.0 mol%, even more preferably 35.0 mol% as the upper limit.

[0019] The SiO2 component is also Na in the sodium ion conductive glass ceramics of the present invention 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is an essential component necessary for including a monoclinic crystal phase and having excellent sodium ion conductivity. It also contributes to improving the denseness (water shielding property) of the sodium ion conductive glass ceramics of the present invention. Therefore, the content of the SiO2 component is 20.0 mol%, preferably 23.0 mol%, more preferably 25.0 mol%, even more preferably 27.0 mol%, and even more preferably 30.0 mol% as the lower limit. Also, Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is likely to form a monoclinic crystal phase, etc., so the content of the SiO2 component is 40.0 mol%, preferably 39.0 mol%, more preferably 37.0 mol%, and even more preferably 35.0 mol% as the upper limit.

[0020] The sodium ion conductive glass ceramics of the present invention may have a configuration composed of the above-described essential components, but further, as optional components, for example, one or more selected from the group consisting of an Al2O3 component, a Y2O3 component, a Sc2O3 component, a CaO component, and a MgO component may be included. Also, as long as it does not significantly affect the sodium ion conductivity of the sodium ion conductive glass ceramics of the present invention, a small amount (for example, a total of 5.0 mol% or less) of a Li2O component or a K2O component may be included.

[0021] The Al2O3 component, the Y2O3 component, and the Sc2O3 component are optional components that can further increase the sodium ion conductivity of the sodium ion conductive glass ceramics of the present invention. Note that the content of the Al2O3 component, the content of the Y2O3 component, and the content of the Sc2O3 component are all preferably 10.0 mol% or less, more preferably 8.0 mol% or less, even more preferably 5.0 mol% or less, and even more preferably 3.0 mol% or less.

[0022] The CaO component and the MgO component are also optional components that can further increase the sodium ion conductivity of the sodium ion conductive glass ceramics of the present invention. Incidentally, the content of the CaO component and the content of the MgO component are both preferably 10.0 mol% or less, more preferably 8.0 mol% or less, still more preferably 5.0 mol% or less, and even more preferably 3.0 mol% or less.

[0023] In addition, it is preferable to minimize the content of sulfur (S) in the sodium ion conductive glass ceramics of the present invention (for example, less than 1 mol%, and even less than 0.1 mol%), and it is more preferable not to contain it. This is because reducing the S component can reduce the possibility of generating harmful gases such as hydrogen sulfide in an aqueous sodium ion secondary battery using the sodium ion conductive glass ceramics of the present invention as an electrolyte diaphragm. Similarly, it is preferable to minimize zinc (Zn), arsenic (As), antimony (Sb), and lead (Pb), and it is more preferable not to contain them because they are harmful substances. Further, from the viewpoint of expressing electronic conductivity, it is also preferable to minimize bismuth (Bi) and tellurium (Te), and it is more preferable not to contain them. In addition, the sodium ion conductive glass ceramics of the present invention are inorganic materials and substantially do not contain hydrocarbon compound components such as resins.

[0024] <Crystal phase and amorphous phase contained in sodium ion conductive glass ceramics> The sodium ion conductive glass ceramics of the present invention have the composition as described above, and further contain a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3). That is, it contains at least a Na having a NASICON structure 1+x Zr2Si x P 3-x O 12It is a sodium ion conductive glass ceramic containing a monoclinic crystal phase represented by (0 < X < 3) and a glassy phase (amorphous phase). The value of X is more preferably 0.1 or more, even more preferably 0.5 or more, and even more preferably 1 or more. The upper limit is more preferably 2.5 or less. In particular, this Na 1+x Zr2Si x P 3-x O 12 When the monoclinic crystal phase represented by (0 < X < 3) is the monoclinic crystal phase represented by Na3Zr2Si2PO 12 That is, when the sodium ion conductive glass ceramic of the present invention contains the monoclinic crystal phase represented by Na3Zr2Si2PO 12 This is very preferable because it is easy to obtain high sodium ion conductivity. Furthermore, in the sodium ion conductive glass ceramic of the present invention, the ratio of the ZrO2 crystal phase (mass ratio of the ZrO2 crystal phase to the total mass of the crystal phase) among all the crystal phases contained (all the crystal phases contained in the sodium ion conductive glass ceramic of the present invention) is 10% by mass or less. With this and the above-described configuration, it is possible to achieve both a dense structure and high sodium ion conductivity. The ratio of the ZrO2 crystal phase is more preferably 9% by mass or less, and even more preferably 8% by mass or less. Here, this "glass ceramic" is obtained by mixing a glass material (amorphous material) and another material and performing heat treatment to synthesize a crystal phase, and includes a crystal phase and an amorphous phase (non-crystalline phase) formed by the heat treatment. That is, it is a mixture of ceramics and glass. The "monoclinic crystal phase" is a type of crystal structure identified by X-ray diffraction measurement, and among the three crystal axes in the crystal structure, two axes are orthogonal, and only the other axis is obliquely intersecting with the above two axes. Alternatively, in the space group, it can be expressed as I2 / a(15) or C2 / c(15). Furthermore, the composition and ratio of the above crystal phase can be measured and analyzed by the powder X-ray diffraction method (the same applies to the composition and ratio of the following crystal phase).

[0025] In particular, for the sodium ion-conductive glass ceramics of the present invention, the composition ratio of Na, Zr, P, and Si in the total of the included crystal phase and amorphous phase (i.e., this glass ceramics) is such that Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is preferably a configuration that satisfies the composition ratio. This means that in the process of crystallization due to sintering during the production of glass ceramics, etc., there is almost no compositional deviation of the crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3). And this also means that the composition ratio represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is more preferably the composition ratio represented by Na3Zr2Si2PO 12 . That is, in the sodium ion-conductive glass ceramics of the present invention, it is more preferable that the composition ratio of Na, Zr, P, and Si satisfies the composition ratio represented by Na3Zr2Si2PO 12 .

[0026] In addition, among all the crystal phases included in the sodium ion-conductive glass ceramics of the present invention, including the monoclinic crystal phase, the ratio of the crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is more preferably 83% by mass or more, even more preferably 85% by mass or more, even more preferably 88% by mass or more, and even more preferably 90% by mass or more. In particular, it is more preferable that the ratio of the crystal phase represented by Na3Zr2Si2PO 12 is within the above range. However, the sodium ion-conductive glass ceramics of the present invention may partially contain other crystal phases.

[0027] Also, because it is easier to increase the sodium ion conductivity, etc., among all the crystal phases included, Na1+x Zr2Si x P 3-x O 12 It is more preferable that the proportion of the monoclinic crystal phase represented by (0 < X < 3) (mass ratio of the crystal phase in the total mass of the crystal phases) is 70% by mass or more, still more preferably 75% by mass or more, and even more preferably 80% by mass or more. In particular, Na3Zr2Si2PO 12 It is more preferable that the proportion of the monoclinic crystal phase represented by is within the above range. Furthermore, although not limited, all Na 1+x Zr2Si x P 3-x O 12 Among the crystal phases represented by (0 < X < 3), it is more preferable that the proportion of the monoclinic crystal phase represented by Na3Zr2Si2PO 12 is 85% by mass or more, still more preferably 88% by mass or more, and even more preferably 90% by mass or more.

[0028] The sodium ion conductive glass ceramics of the present invention is a glass material powder having a sodium ion conductivity of 1.0×10 -6 S / cm or less at 25°C, and a crystal material powder containing a ZrO2 component having a sodium ion conductivity of less than 1.0×10 -8 S / cm (including those having substantially no sodium ion conductivity) such as zirconia powder, which are mixed and sintered. It is more preferable that the Na 1+x Zr2Si x P 3-x O 12 The compositional deviation of the monoclinic crystal phase represented by (0 < X < 3) is less likely to occur (the ZrO2 component of the crystal material powder is Na 1+x Zr2Si x P 3-x O 12(It is easy to contribute to the formation of a monoclinic crystal phase represented by (0 < X < 3), and it is easy to form glass ceramics that have a dense structure and high sodium ion conductivity. Therefore, it is easy to form a dense electrolyte membrane. As such glass material powder, the powder of the glass material for synthesizing sodium ion conductive glass ceramics of the present invention described later is preferably exemplified. Further, the crystal material powder containing a ZrO2 component preferably contains more than 30 mol% of the ZrO2 component.)

[0029] And, as described above, the sodium ion conductive glass ceramics of the present invention contain a certain amount or more of an amorphous phase together with the above-described crystal phase, have a dense structure, and have high water shielding properties. And this water shielding property exhibits its effect over a long period of time. The ratio (content ratio) of this amorphous phase is not limited, but in the sodium ion conductive glass ceramics of the present invention, it is more preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 20% by mass or more. The upper limit is preferably less than 50% by mass, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The ratio of this amorphous phase can be measured, for example, by forming the sodium ion conductive glass ceramics of the present invention into a sheet shape (sheet-shaped sintered body) having a film thickness (thickness) of 1 μm or more and 1000 μm or less, breaking and polishing this to obtain a fracture surface, and calculating the ratio of the amorphous phase in this fracture surface in terms of area (calculating the ratio occupied by the area of the amorphous phase in the entire area of this fracture surface). Note that this "film thickness (thickness)" is the linear distance between both surfaces (main surfaces) of the sheet-shaped sintered body, and is a value obtained by measuring the film thickness at any 10 locations using a known device and calculating the average value. The same applies hereinafter.

[0030] Further, the water shielding property of the sodium ion conductive glass ceramics of the present invention is not limited, but when the sodium ion conductive glass ceramics of the present invention are used as a sheet-shaped or plate-shaped substrate, the unit area of this substrate (the unit area of the main surface, 1 cm 2) and a leak rate per mm of thickness of 10.0 μL / h or less. The upper limit is more preferably 8.0 μL / h or less, even more preferably 5.0 μL / h or less, and even more preferably 2.0 μL / h or less. Here, the "leak rate" is defined as the rate at which water (liquid water) leaks (permeation amount, μL) through the above-mentioned substrate is measured using the device shown in FIG. 1 (pellet leak checker using water column pressure), with the evaluation value evaluated using a glass plate with absolutely no water permeability as the baseline, in a thermostatic chamber controlled at 25°C, over a period of 3 to 5 days for one sample, and the rate per unit area (1 cm) per hour. 2 ) and the calculated amount of water leakage per mm of thickness. The water column pressure used is 250mmAq to 50mmAq. In order to reduce the error due to the atmosphere in the container, the amount of air in the container is reduced as much as possible, and atmospheric pressure correction is also performed. Alternatively, the sodium ion conductive glass ceramics of the present invention can reduce the amount of leaked water (per unit area (1 cm2) per hour) 2 When the electrolysis of water caused by the leakage current per mm of the substrate and the water leaked per mm of thickness occurs and is converted into a current, the current per unit area and thickness of the substrate is preferably 15 μA or less, more preferably 10 μA or less, and even more preferably 2 μA or less. This current may be directly evaluated by an electrochemical method.

[0031] Furthermore, the sodium ion conductive glass ceramics of the present invention have high sodium ion conductivity in addition to high water impermeability. The sodium ion conductivity at 25° C. is 6.0×10 -4 S / cm or more, and 7.0×10 -4 More preferably, it is 8.0×10 S / cm or more. -4 More preferably, it is 9.0×10 S / cm or more. -4 More preferably, it is 1.0×10 S / cm or more. -3 It is more preferable that the viscosity is at least S / cm.

[0032] <Electrolyte membrane for aqueous sodium-ion secondary batteries containing sodium-ion conductive glass ceramics> The sodium ion conductive glass ceramic of the present invention has high water-blocking property and high sodium ion conductivity as described above, and further has water resistance, so that it can be suitably used as an electrolyte membrane for aqueous sodium ion secondary batteries (a solid electrolyte membrane arranged between the positive and negative electrodes of an aqueous sodium ion secondary battery to separate an aqueous electrolyte). In other words, the electrolyte membrane for aqueous sodium ion secondary batteries of the present invention containing the sodium ion conductive glass ceramic of the present invention has excellent water-blocking property and sodium ion conductivity, and is useful as an electrolyte membrane for aqueous sodium ion secondary batteries. The content of the sodium ion conductive glass ceramic of the present invention in the electrolyte membrane for aqueous sodium ion secondary batteries of the present invention may be more than 50 mass%, more preferably 60 mass% or more, and even more preferably more than 65 mass%.

[0033] The shape of the electrolyte membrane for an aqueous sodium ion secondary battery of the present invention is not limited as long as it functions as a membrane, but it is more preferable that the shape (overall shape) be cylindrical, one-side sealed cylindrical, elliptical one-side sealed tubular, honeycomb-structured tubular, or plate-like. Here, "cylindrical" refers to a cylindrical shape in which the top and bottom surfaces are approximately circular (approximately circular with a ratio of the major axis to the minor axis of less than 1.5) and unsealed (there is no diaphragm on either the top or bottom surfaces), with the side surfaces forming the circumference of the cylinder functioning as a diaphragm; "one-sided sealed cylindrical" refers to the above-mentioned cylindrical shape in which one of the top and bottom surfaces is sealed with a diaphragm and the other is unsealed; "elliptical one-sided sealed cylindrical" refers to the above-mentioned one-sided sealed cylindrical shape in which both the top and bottom surfaces are elliptical (an ellipse with a ratio of the major axis to the minor axis of 1.5 or more) and sealed on one side; "honeycomb-structured cylindrical" refers to a cylindrical shape in which the internal cavity has a honeycomb structure; and "plate-shaped" refers to a plate shape (plate sheet-shaped) having two main surfaces, the front and back surfaces, and functioning as a diaphragm.

[0034] The membrane thickness of the electrolyte membrane for aqueous sodium ion secondary batteries of the present invention is not limited either, but is preferably 0.01 mm or more, more preferably 0.1 mm or more. The upper limit is preferably 1 mm or less, more preferably 0.5 mm or less. This "membrane thickness" is also the linear distance between both surfaces (main surfaces) of the electrolyte membrane for aqueous sodium ion secondary batteries, and is a value obtained by measuring the membrane thickness at any 10 points using a known device and calculating the average value. Furthermore, the density is not particularly limited, but is, for example, 2.0 g / cm 3 or more, 2.5 g / cm 3 or more, 3.0 g / cm 3 or more, 3.1 g / cm 3 The sodium ion conductive glass ceramics of the present invention having the same density as above may be used to form the electrolyte membrane for an aqueous sodium ion secondary battery of the present invention having the above density. The electrolyte membrane for aqueous sodium ion secondary batteries of the present invention may be bonded to a porous support plate so as to maintain its thinness and strength.

[0035] <Components and composition of glass materials for the synthesis of sodium ion conductive glass ceramics> Next, the components and composition of the glass material for synthesizing the sodium ion conductive glass-ceramics of the present invention, which can be synthesized by mixing and sintering with a crystal material containing the ZrO2 component, will be described in detail.

[0036] The Na2O component is an essential component necessary for imparting sodium ion conductivity to the sodium ion conductive glass ceramics of the present invention synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention. Therefore, the content of the Na2O component is 30.0 mol%, preferably 31.0 mol%, more preferably 33.0 mol%, still more preferably 35.0 mol%, and still more preferably 36.0 mol% as the lower limit. On the other hand, since the sodium ion conductive glass ceramics of the present invention synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention tend to form a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3), the content of the Na2O component is 40.0 mol%, preferably 39.0 mol%, and more preferably 38.0 mol% as the upper limit.

[0037] The P2O5 component is an essential component necessary for the sodium ion conductive glass ceramics of the present invention synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention to contain a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) and have excellent sodium ion conductivity. Therefore, the content of the P2O5 component is 5.0 mol%, preferably 8.0 mol%, more preferably 10.0 mol%, and still more preferably 12.0 mol% as the lower limit. Also, since the sodium ion conductive glass ceramics of the present invention synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention tend to form a monoclinic crystal phase represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3), the content of the P2O5 component is 35.0 mol%, preferably 30.0 mol%, more preferably 25.0 mol%, still more preferably 22.0 mol%, still more preferably 20.0 mol%, and still more preferably 15.0 mol% as the upper limit.

[0038] The SiO2 component is also synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention. The sodium ion conductive glass ceramics of the present invention has Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3), which is an essential component necessary for having a monoclinic crystal phase and excellent sodium ion conductivity. It also contributes to improving the denseness (water shielding property) of the synthesized sodium ion conductive glass ceramics of the present invention. Therefore, the content of the SiO2 component is 30.0 mol%, preferably 33.0 mol%, more preferably 35.0 mol%, still more preferably 38.0 mol%, still more preferably 40.0 mol%, still more preferably 42.0 mol%, and still more preferably 45.0 mol% as the lower limit. Also, since the sodium ion conductive glass ceramics of the present invention synthesized using the glass material for synthesizing sodium ion conductive glass ceramics of the present invention is likely to form a monoclinic crystal phase of Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3), the content of the SiO2 component is 60.0 mol%, preferably 56.0 mol%, more preferably 53.0 mol%, and still more preferably 50.0 mol% as the upper limit.

[0039] The ZrO2 component is an optional component that may be included in the glass material for synthesizing sodium ion conductive glass ceramics of the present invention. By containing the ZrO2 component, the water resistance of the glass material can be enhanced. However, from the viewpoint of facilitating glass formation of the glass material for synthesizing sodium ion conductive glass ceramics of the present invention, the content of the ZrO2 component in the glass material for synthesizing sodium ion conductive glass ceramics of the present invention is preferably 5.0 mol%, more preferably 3.0 mol%, and even more preferably 1.0 mol% as the upper limit. And it may be substantially free of the ZrO2 component.

[0040] The glass material for synthesizing sodium ion conductive glass ceramics of the present invention may have a composition consisting of the essential components described above. However, as an optional component, in addition to the ZrO2 component, for example, as described above, one or more selected from the group consisting of Al2O3 component, Y2O3 component, Sc2O3 component, CaO component, and MgO component may be included. Further, as long as it does not affect the sodium ion conductivity of the sodium ion conductive glass ceramics of the present invention synthesized using this, a small amount of Li2O component or K2O component may be contained. These contents may be the same as the contents of the sodium ion conductive glass ceramics of the present invention described above. Furthermore, similar to the sodium ion conductive glass ceramics of the present invention described above, sulfur (S), zinc (Zn), arsenic (As), antimony (Sb), lead (Pb), bismuth (Bi), or tellurium (Te) is preferably reduced as much as possible, and more preferably not contained.

[0041] And the glass material for synthesizing sodium ion conductive glass ceramics of the present invention contains each component as described above. Further, the composition ratio of Na, P, and Si satisfies the composition ratio excluding Zr among the composition ratios represented by Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3). The value of X may be the same as described above. Thereby, it becomes possible to synthesize the sodium ion conductive glass ceramics of the present invention as described above by mixed sintering with a crystal material containing a ZrO2 component. In particular, when the composition ratio represented by this Na 1+x Zr2Si x P 3-x O 12 (0 < X < 3) is the composition ratio represented by Na3Zr2Si2PO 12 That is, when the composition ratio of Na, P, and Si satisfies the composition ratio excluding Zr among the composition ratios represented by Na3Zr2Si2PO 12 The sodium ion conductive glass ceramics of the present invention obtained by mixed sintering with a crystal material containing a ZrO2 component is Na3Zr2Si2PO 12This is highly preferred because it is easy to obtain a high sodium ion conductivity and the like.

[0042] Furthermore, the glass material for synthesizing sodium ion conductive glass-ceramics of the present invention preferably contains 5 mol % or less, more preferably 3 mol % or less, of the above-mentioned components capable of imparting water resistance to the glass material, such as Al2O3, Y2O3, and ZrO2. This is because the increased water resistance increases the freedom of the manufacturing method, improves storage properties, and allows for easy storage, resulting in increased stability of quality and reduced costs. The total content of these components that impart water resistance (e.g., Al2O3, Y2O3, and ZrO2) may be 20 mol% or less, more preferably 10 mol% or less. If the amount of these added components is too large, when the sodium ion conductive glass ceramic is made by mixing and sintering with a crystalline material containing the ZrO2 component, composition deviation occurs, and the sodium ion conductivity and density tend to decrease.

[0043] Furthermore, the glass material for synthesizing a sodium ion conductive glass ceramic of the present invention has a glass transition temperature (Tg) of preferably 600°C or higher, more preferably 650°C or higher, even more preferably 680°C or higher, and even more preferably 730°C or higher, since the sodium ion conductive glass ceramic of the present invention can be easily synthesized. The upper limit may be 900°C or lower, 850°C or lower, or 800°C or lower. For the same reason, the crystallization temperature (Tc) is preferably 650°C or higher, more preferably 700°C or higher, even more preferably 720°C or higher, and even more preferably 780°C or higher. The upper limit may be 950°C or lower, 900°C or lower, or 850°C or lower.

[0044] The glass material for synthesizing sodium ion conductive glass ceramics of the present invention, which has the above-mentioned components and composition, is an amorphous material. Therefore, the glass material for synthesizing sodium ion conductive glass ceramics of the present invention does not substantially contain a crystalline phase. Moreover, the form of the glass material for synthesizing sodium ion conductive glass ceramics of the present invention is preferably in powder form, as described below.

[0045] <Manufacturing method etc.> Next, the sodium ion conductive glass ceramic of the present invention, an electrolyte membrane for an aqueous sodium ion secondary battery containing the same, and a method for producing the glass material for synthesizing the sodium ion conductive glass ceramic of the present invention used in the synthesis thereof will be described in detail.

[0046] First, a method for producing the glass material for synthesizing sodium ion conductive glass ceramics of the present invention will be described. The glass material for synthesizing sodium ion conductive glass ceramics of the present invention can be produced by a general method for producing amorphous inorganic materials, such as firing, melting, and vitrification of inorganic materials. The melting temperature when melting is performed after pre-firing is not limited, but is preferably 1000°C or higher, and more preferably 1200°C or higher and 1450°C or lower. The inorganic material used for production is also not limited, but it is preferable to use disodium hydrogen phosphate (NaH2PO4), sodium carbonate (Na2CO3), orthophosphoric acid (H3PO4), silicon oxide (SiO2), etc. Here, in the glass material for synthesizing sodium ion conductive glass ceramics of the present invention, the content of the ZrO2 component must be 5.0 mol % or less as described above, from the viewpoint of facilitating vitrification.

[0047] The sodium ion conductive glass ceramics of the present invention and the electrolyte membrane for aqueous sodium ion secondary batteries containing the same can be obtained by mixing the glass material for synthesizing the sodium ion conductive glass ceramics of the present invention obtained as described above with a crystalline material containing a ZrO2 component (e.g., zirconia oxide powder, etc.), forming (e.g., pressure forming) into a film or the like as necessary, and sintering at a sintering temperature of, for example, 1000°C or higher and lower than 1250°C. In particular, since it is easy to achieve both denseness and sodium ion conductivity, the sintering temperature is more preferably 1100°C or higher and 1200°C or lower. If the sintering temperature is higher than 1250°C, the formation of a ZrO2 crystalline phase due to thermal decomposition tends to occur easily.

[0048] It is preferable that the glass material for synthesizing the sodium ion conductive glass ceramics of the present invention and the crystalline material containing the ZrO2 component are both in powder form (powder), since this facilitates the above-mentioned mixing and molding. For example, the average particle diameter (D 90 ) is preferably 3 μm or less, more preferably 2.5 μm or less, and even more preferably 2 μm or less. In addition, after mixing, they may be pulverized to have the above average particle diameter. Here, this "average particle diameter" refers to the volume-based average particle diameter (volume cumulative distribution 90% diameter (D 90 )) The same applies below.

[0049] As described above, the sodium ion conductivity of the glass material powder for synthesizing sodium ion conductive glass ceramics of the present invention at 25° C. is 1.0×10 -6 The crystalline material powder containing the ZrO2 component has a sodium ion conductivity of 1.0×10 S / cm or less at 25°C. -8 In other words, the sodium ion conductivity of the sodium ion conductive glass ceramic of the present invention at 25° C. is preferably less than 1.0×10 -6The glass material powder for synthesizing sodium ion conductive glass ceramics of the present invention has a sodium ion conductivity of 1.0×10 S / cm or less at 25° C. -8 It is preferable that the powder is made by mixing and sintering a crystalline material powder containing a ZrO2 component having a viscosity of less than S / cm.

[0050] The embodiment described above is merely an example for facilitating understanding of the present invention, and is not intended to limit the present invention. In other words, the components and the like described above may be modified or improved without departing from the spirit of the present invention, and the present invention naturally includes equivalents thereof.

[0051] Hereinafter, examples of the present invention will be described, however, the present invention is not limited to the following examples, and various modifications are possible within the technical concept of the present invention. EXAMPLES

[0052] <Preparation of sodium ion conductive glass ceramics and comparative samples> The sodium ion conductive glass ceramics were produced by preparing raw glass (glass material for synthesizing sodium ion conductive glass ceramics), mixing it with zirconia (crystalline material containing ZrO2), molding and sintering it. Specifically, it was produced by the following method.

[0053] The raw materials NaH2PO4, Na2CO3, and SiO2 were mixed to have the composition ratios shown in Table 1 below in mol% calculated as oxides, then placed in a vinyl bag, gently shaken to mix, and placed in a platinum pot and pre-fired at 1000°C for 1 hour. After this pre-fire, the mixture was melted in a melting furnace at 1300°C or higher while stirring thoroughly, and cast onto a metal casting plate. The mixture was then pulverized to a size of 106 μm mesh pass or less using a stamp mill, to obtain the raw glass of Examples 1 to 4.

[0054] [Table 1]

[0055] The thermal properties (glass transition temperature Tg, crystallization temperature Tc) of each of the obtained raw glasses were measured using a differential thermal analyzer (NETZSCH, STA409PC). The results are shown in Table 2 below. The sodium ion conductivity at 25°C was 1.0×10 -6 S / cm or less.

[0056] [Table 2]

[0057] The above-mentioned ground raw glass materials (ground products passing a 106 μm mesh) and zirconia powder (manufactured by Daiichi Kigenso Kagaku Kogyo Co., Ltd., UEP-100: substantially no sodium ion conductivity) were mixed to the stoichiometric ratios shown in Table 3 below, and ground in a planetary ball mill (manufactured by Fritsch Japan, P-5) using 1-propanol, φ2 mm zirconia beads (manufactured by Nikkato, YTZ beads), and a 500 cc zirconia pot at 250 rpm for 2 hours (ground for 5 minutes, rest for 1 minute). The average particle size of the ground slurry was measured using a particle size distribution meter (laser diffraction particle size distribution measuring device, manufactured by Spectris). All of these average particle sizes were D 90 It was confirmed that the particles were sufficiently pulverized to a size of 2 μm or less. The pulverized slurry was separated from the zirconia beads using a sieve, and the obtained slurry was dried using a shelf-type solvent recovery dryer (manufactured by Sozo Kagaku Kogyo Co., Ltd.).

[0058] On the other hand, as a comparison sample, Na3Zr2Si2PO 12 The slurry was ground in a planetary ball mill (Fritsch Japan, P-5) using 1-propanol, φ2 mm zirconia beads (Nikkato, YTZ beads), and a 500 cc zirconia pot at 250 rpm for 2 hours (5 minutes of grinding, 1 minute of rest). The average particle size of the ground slurry was measured using a particle size distribution meter (laser diffraction particle size distribution measuring device, Spectris). This average particle size was D 90It was confirmed that the particles were sufficiently pulverized to have a particle size of 2 μm or less. After separating the pulverized slurry from the zirconia beads using a sieve, the obtained slurry was dried using a shelf-type solvent recovery dryer (manufactured by Sozo Kagaku Kogyo Co., Ltd.) (Comparative Example 1).

[0059] In addition, to compare with the case where a sintering aid was used, a sample was prepared using a sodium ion conductive glass electrolyte (50 mol% Na2O-9 mol% SiO2-41 mol% P2O5) as a sintering aid. 12 The sodium ion conductive glass electrolyte was added at a ratio of 10 wt% to the slurry, and the mixture was ground in a planetary ball mill (Fritsch Japan, P-5) at 250 rpm for 2 hours (5 minutes of grinding, 1 minute of rest) using 1-propanol, φ2 mm zirconia beads (Nikkato, YTZ beads), and a 500 cc zirconia pot. The average particle size of the ground slurry was measured using a particle size distribution meter (laser diffraction particle size distribution measuring device, Spectris). This average particle size was D 90 It was confirmed that the particles were sufficiently pulverized to have a particle size of 2 μm or less. After separating the pulverized slurry from the zirconia beads using a sieve, the obtained slurry was dried using a shelf-type solvent recovery dryer (manufactured by Sozo Kagaku Kogyo Co., Ltd.) (Comparative Example 2). Table 3 below shows the compositions in mol % calculated as oxides, and the composition formulas showing the composition ratios of Na, Zr, P, and Si.

[0060] [Table 3]

[0061] Each of the above dried powders (including parts that became slightly lumpy due to the drying process) was crushed to a 500 μm mesh using an alumina mortar and an alumina pestle, and then 1 g of each was taken and molded using a φ20 mm molding die under a pressure of 20 kN to obtain multiple pellets (sheet-like pellets).

[0062] The pellets were cooled to a density of 3.0 g / cm 3The pellets were heat-treated for 1 hour at sintering temperatures ranging from 1100°C to 1250°C so as to satisfy conditions exceeding the limit of 100°C. Various sintered pellets (sheet-shaped sintered pellets) were obtained as solid electrolytes for measuring sodium ion conductivity and water barrier properties. The surfaces of these sintered pellets were polished using #800, #2000, #5000, and #8000 waterproof abrasive paper and 1-propanol, and the thickness (mm), diameter (mm), and weight (g) were measured using a caliper, micrometer, and electronic balance, respectively, and the density (g / cm 3 ) was calculated. The results are shown in Table 4 below. Even under the optimized heat treatment temperature conditions, Example 1 showed the highest density, and the other Examples also showed higher values ​​than the Comparative Examples.

[0063] [Table 4]

[0064] <Sodium ion conductivity measurement> The sodium ion conductivity of each sintered pellet after polishing was measured by forming gold electrodes as blocking electrodes on both sides of the sintered pellet after density measurement using a magnetron sputtering device (SC-701HMC, manufactured by Sanyu Electronics Co., Ltd.), and measuring impedance at 25°C under conditions of a frequency of 0.1 Hz to 7 MHz, an amplitude voltage of 10 mV, and an open circuit voltage using an electrochemical evaluation device (SP300, manufactured by Biologic Co., Ltd.), and calculating the sodium ion conductivity (mS / cm) at 25°C. The measurement results are also shown in Table 4 above. The sodium ion conductivity was 1.04 mS / cm (1.04 x 10 -3 S / cm), which was about three times that of Comparative Example 2, which had the same composition, and about twice that of Comparative Example 1. The other Examples also had higher values ​​than the Comparative Examples. On the other hand, Comparative Example 2 had the lowest sodium ion conductivity. It is presumed that only Comparative Example 2 contained the addition of a sodium ion conductive glass electrolyte as a sintering aid, which caused a deviation in the composition after sintering, which is thought to be the cause of the increased resistance within the grains and at the grain boundaries.

[0065] <Water impermeability measurement> The water impermeability of each sintered pellet after polishing was evaluated by measuring the leak rate using the device shown in FIG. 1. The above-mentioned gold electrodes were not used because they may cause changes in water impermeability, and the sintered pellets (sheet-shaped substrates) after density measurement were used. In order to reduce the atmospheric error in the container in FIG. 1, the air in the container was reduced as much as possible, and atmospheric pressure correction was also performed. A Pyrex (registered trademark) glass plate, which has no gas permeability or water permeability, was also evaluated and used as the baseline. The device was placed in a thermostatic chamber controlled at 25°C and measurements were performed. Measurements of one sample were evaluated over 3 to 5 days. The water column pressure used was 250 mmAq to 50 mmAq. The measurement results of Comparative Examples 1 to 2 and Examples 1 to 4 (results converted into values ​​per unit area and thickness per mm per hour) are shown in Table 5 below. The measurement results (actual values) of Comparative Example 2 and Example 3 are also shown in FIG. 2.

[0066] [Table 5]

[0067] From this result, the leakage rate of Comparative Example 1 was 338 μL / h, which was a significant leakage. Although the leakage rate of Comparative Example 2 was improved to about 1 / 20 of Comparative Example 1 (18 μL / h), it was confirmed that there was leakage at a clearly detectable level. On the other hand, in Examples 1 to 4, the leak rate was 0.6 to 1.5 μL / h, with an average of 1 μL / h, which was a very low value. In the evaluation results for Pyrex (registered trademark) glass, the leak rate was 1.2 to 2.8 μL / h, with an average of 1.7 μL / h, so these are considered to be evaluation results close to the lower limit of detection. 2 Regarding the effect of a leak rate of 1 μL / h per unit time, if we interpret the results by assuming that the electrical energy stored in the active material is consumed by the electrolysis of the leaked water, the active material used in the battery has a discharge capacity of 110 mAh / g, equivalent to LiMn2O4, which is generally considered to be low, and a density of 4.2 g / cm3. 3 Since it is a water-based material, the filling ratio of the active material is high at 80%, and if the film thickness is 1 mm, the unit area of ​​1 cm2 The current capacity per unit time is 37 mAh. The leakage amount of 1 μL / h is converted to 1.5 μA from the electrolysis of water, and if the current capacity of 37 mAh is divided by 1.5 μA as the leakage current, the self-discharge rate per month is 2.9%. In general, the self-discharge rate per month of the same aqueous nickel-hydrogen battery is 10 to 30%, so it is considered that up to 10 μL / h is within the practical acceptable range, although it depends on the electrode layer thickness, etc. From the above, it was confirmed that not only Comparative Example 1 but also Comparative Example 2 with a leakage amount of 18 μL / h is insufficient as an electrolyte membrane, while Examples 1 to 4 all fully meet that range.

[0068] <Crystal Phase Analysis> The composition of the crystal phase of each of the sintered pellets produced was analyzed by powder X-ray diffraction measurement. Each sample was not crushed, but the polished surface was analyzed. A Bruker X-ray diffraction measurement device (D8 DISCOVER) was used, with a tube voltage of 40 kV and 40 mA, and a Cu tube (CuKα radiation) as the X-ray source. Rietveld diffraction measurement software (TOPAS) was used to confirm the composition ratio. Comparative Example 1, Comparative Example 2, and Example 3 were evaluated. The measurement results for Example 3 are shown in Figure 3. The identified crystal phase composition was monoclinic Na3Zr2Si2PO 12 , rhombohedral Na3Zr2Si2PO 12 , monoclinic ZrO2, tetragonal NaPO3, and monoclinic Zr(HPO4)2 were confirmed. The results of Comparative Example 1, Comparative Example 2, and Example 3 are shown in Table 6 below (units are mass %). Example 3 is monoclinic Na3Zr2Si2PO with high sodium ion conductivity. 12 The proportion of rhombohedral Na3Zr2Si2PO 12 The proportion of zirconia with low sinterability was smaller. ZrO2 was not detected in the pre-sintered powders of Comparative Examples 1 and 2, but it is presumed that a ZrO2 crystal phase was formed by thermal decomposition during sintering.

[0069] [Table 6]

[0070] <Microstructure Observation I> The microstructure of the obtained sintered pellets was observed using a scanning electron microscope (JSM-IT700HR / LA, manufactured by JEOL Ltd.). The evaluation subjects were Comparative Example 1, Comparative Example 2, and Example 3. The results of SEM observation (secondary electron images) of the fracture surfaces of these sintered pellets are shown in Figs. 4 to 9.

[0071] As shown in Fig. 4, in Comparative Example 1, the presence of pores of 10 to 100 µm was confirmed. In addition, as shown in the enlarged view of Fig. 5, coarse and small gaps were confirmed around the pores. It is considered that the water impermeability was significantly impaired by these large pores and the gaps observed around the pores. In addition, the density was 3.01 g / cm3 despite the high proportion of high-density ZrO2 crystal phase in the XRD measurement results. 3 The reason why the ZrO2 crystal phase is still small is presumably due to the increased formation of ZrO2 crystal phase and porosity caused by thermal decomposition. In Comparative Example 2, which was produced using a sintering aid, an improvement was observed compared to Comparative Example 1, but scattered pores were still observed, and even in the enlarged image, it was confirmed that the pores and their surrounding areas were rough and had gaps (FIGS. 6 and 7).

[0072] On the other hand, in Example 3, almost no pores were observed as shown in Figure 8, and even when enlarged, no small gaps were observed as shown in Figure 9. In other words, it was confirmed that a dense structure was obtained and that the material had sufficient water impermeability.

[0073] <Sheet molding test> In industrial production of products, molding from a slurry containing a binder, such as sheet molding or extrusion molding, and sintering may be performed, so a sheet molding test was performed to confirm whether a good dispersion state can be maintained even in that state. Example 5 was used using the powder after crushing and drying of Example 3, and Comparative Example 3 was used using the powder after crushing and drying of Comparative Example 2.

[0074] For each powder after pulverization and drying, 100 g of 1-propanol, 75.5 g of dispersing agent (Kyoeisha Chemical Co., Ltd., Floren G-700), 2.4 g of binder (Kyoeisha Chemical Co., Ltd., Oricox 2427: acrylic polymer with very little ash remaining after sintering), 26.25 g of plasticizer (Ito Oil Mills, DOS), and 0.14 g of wetting agent (Kyoeisha Chemical Co., Ltd., KL100) were mixed and kneaded for 12 hours in a pot mill using zirconia beads (Nikkato Corporation, YTZ beads) of φ10 mm and φ2 mm as media. After kneading, the zirconia beads and the slurry were separated, and then the mixture was degassed for 5 minutes at 1000 rpm and 150 Torr using a foam remover (Thinky Corporation, ARV-200), and then formed into a sheet by the doctor blade method. The film thickness of the formed sheet was 25 μm. Thirteen of these sheets were stacked and vacuum-packed, and then isostatically pressed at 60 MPa and sintered at a sintering temperature between 1100°C and 1200°C. The density and sodium ion conductivity of the sintered sheet laminate (sintered sheet) showed almost the same values ​​as those of the aforementioned compacted powder.

[0075] <Microstructure Observation II> The microstructure of the obtained sheet laminate (sheet sintered body) was observed using a scanning electron microscope (JSM-IT700HR / LA, manufactured by JEOL Ltd.). The results of SEM observation of the fracture surface of this sheet laminate (sheet sintered body) are shown in Figs. 10 and 11. Backscattered electron image observation was performed to determine the composition of the sample. The black areas represent the amorphous phase, and the white areas represent the crystalline phase. In Example 5, the black amorphous phase was clearly observed (approximately 20-30% in terms of area on the fracture surface, Fig. 10). As a result of EDS measurement, no uneven distribution of Zr, Si, Na, etc. was observed. As the material diffuses and sinters at high temperatures, the target composition Na3Zr2Si2PO 12 It is believed that the crystal structure is formed and takes on both an amorphous and a crystalline state.

[0076] On the other hand, in Comparative Example 3 in Fig. 11, the presence of crystals was observed throughout the sample, and it was presumed that the sintering aid was incorporated into the crystals. Many air bubbles were also observed. The amorphous phase was not sufficiently maintained (less than 10% in terms of area on the fracture surface), and it was confirmed from the microstructure observation that this was the reason why a water-resistant dense film could not be formed.

Claims

1. In terms of oxide, mol% is Na 2 O component is 20.0 to 27.0%, ZrO 2 Ingredients: 30.0-40.0%, P 2 O 5 Ingredients: 3.0-20.0%, SiO 2 Ingredients: 20.0 to 40.0% Contains Na 1+x Zr 2 S x P 3-x O 12 (0<X<3) and, among all the crystal phases contained, ZrO 2 The proportion of the crystalline phase is 10% by mass or less; Sodium ion conducting glass-ceramics.

2. The composition ratio of Na, Zr, P, and Si in the sodium ion conductive glass ceramics is Na 1+x Zr 2 S x P 3-x O 12 2. The sodium ion conductive glass ceramic according to claim 1, which satisfies the composition ratio represented by (0<X<3).

3. 3. The sodium ion conductive glass ceramic according to claim 1 or 2, wherein, when the sodium ion conductive glass ceramic is used as a sheet or plate-shaped substrate, the leakage rate per unit area and 1 mm thickness of the substrate is 10.0 μL / h or less, or the amount of current when water electrolysis occurs due to water leaking through the substrate per unit area and 1 mm thickness per hour is 15 μA or less per unit area and 1 mm thickness of the substrate.

4. Sodium ion conductivity at 25°C is 6.0 x 10 -4 The sodium ion conductive glass ceramic according to claim 1 or 2, having a viscosity of 1.0 S / cm or more.

5. Sodium ion conductivity at 25°C is 1.0 x 10 -6 A glass material powder having a sodium ion conductivity of 1.0×10 S / cm or less at 25° C. -8 ZrO 2 The sodium ion conductive glass ceramic according to claim 1 or 2, which is obtained by mixing and sintering a crystalline material powder containing the component.

6. Of all the crystal phases contained, the Na 1+x Zr 2 S x P 3-x O 12 3. The sodium ion conductive glass ceramic according to claim 1, wherein the proportion of a monoclinic crystal phase represented by (0<X<3) is 70 mass % or more.

7. 3. The sodium ion conductive glass ceramic according to claim 1, wherein the proportion of an amorphous phase is 10 mass % or more.

8. 3. An electrolyte membrane for an aqueous sodium ion secondary battery, comprising the sodium ion conductive glass ceramic according to claim 1 or 2.

9. In terms of oxide, mol% is Na 2 O component 30.0 to 40.0%, ZrO 2 Ingredients: 0-5.0%, P 2 O 5 Ingredients: 5.0-35.0%, SiO 2 Ingredients: 30.0 to 60.0% Contains The composition ratio of Na, P, and Si is Na 1+x Zr 2 S x P 3-x O 12 The composition ratio satisfies the formula (0<X<3) excluding Zr. A glass material for the synthesis of sodium ion conductive glass-ceramics.

Citation Information

Patent Citations

  • Aqueous solution secondary battery

    JP2011086402A

  • Aqueous solution based secondary battery

    JP2012003928A

  • Aqueous solution system secondary battery

    JP2012054208A

  • Water barrier sodium ion conductive film and sodium battery

    JP2017124951A